Patterns And Risk Factors Of OTC Medication Misuse Among Saudi Youth And Strategies For Community-Pharmacy Intervention (The Review of Diabetic Studies, 2024)
Over-the-counter (OTC) medication misuse is an emerging public health concern among youth, with potential implications for safety and long-term health outcomes. This study investigated the prevalence, patterns, and determinants of OTC medication misuse among Saudi youth and explored the role of community pharmacists in mitigating such behaviors. Findings indicate that a substantial proportion of participants engaged in misuse behaviors, including prolonged use, concurrent consumption of multiple OTC products, and inconsistent adherence to medication instructions. Multilevel factors contributed to misuse, encompassing individual cognitive perceptions, interpersonal influences from peers and family, and system-level determinants such as unrestricted accessibility and persuasive pharmaceutical advertising. Participants demonstrated high trust in community pharmacists and a strong willingness to receive counseling and participate in pharmacist-led educational interventions, highlighting the strategic role of pharmacies in preventive efforts. The study underscores the need for comprehensive, multilevel interventions that combine education, social norm reinforcement, and structural measures to promote safe OTC medication practices and cultivate responsible self-medication behaviors among Saudi youth.